Innate immune cells and T CD4 cells profile during hepatitis B among HIV co-infection Beninese - LOKOSSOU, GATIEN; Adegbindin, Rafiou; SENOU, MAXIMIN (My University, 2022)
Background: Worldwide, human immunodeficiency virus (HIV) infection remains a real public health. Hepatitis B virus (HBV) and HIV have the same routes of transmission and shared risk factors and epidemiology similarities. The purpose of this study was to assess the impact of HBV and HIV co-infection on T CD4 cells and innate immune cells. Methods: A cross-sectional and descriptive study was carried among 260 persons living with HIV (PLHIV) admitted and supported with antiviral tri therapy at the national reference center for research and Care of HIV infected person (NRCRC) of the national hospital and university center in Cotonou, Benin. After PLHIV peripheral blood collection, surface hepatitis B antigens (HBsAg) and HIV serology were tested using ELISA (Enzyme linked immuno sorbent assay). White blood cell count and leukocyte formula were performed using flow cytometry. After staining with anti CD4 antibodies, TCD4+ lymphocytes frequency was determined using flow cytometry. Means were calculated using student T test. Results: Of the 260 PLHIV, 10.77% (n=28) were co-infected with HBV. Our data has shown a significant decrease of lymphocytes among HIV and HBV co-infected persons and a very significant increase in immune innate cells including eosinophils, polynuclear basophils and monocytes, suggesting an important role of innate immune cells during HIV and HBV coinfection. Conclusion: HIV and HBV coinfection results in hyperinflammatory response associated with viral clearance. How this hyperinflammatory response is mounted was still unclear. More data are needed for better management of HIV and HBV co-infection.
Keywords: Innate immune cells; HIV; HBV; Co-infection; Benin